Фінансово-правові засади соціального захисту військовослужбовців - Гетманець, О. П.; Hetmanets , O. P.; Гетманець Ольга Петрівна (Вісник Харківського національного університету внутрішніх справ. – 2023. – № 3 (102), ч. 1. - С. 102-110, 2023)
На підставі аналізу чинного законодавства щодо фінансування соціальних виплат військовослужбовцям та практики його застосування визначено проблемні питання їх фінансово-правового забезпечення. Наголошено, що реалізація соціальної функції держави щодо задоволення особливих потреб військових залежить від удосконалення бюджетного процесу на стадіях складання проєкту бюджету, розгляду та затвердження закону про Державний бюджет України. Визначено, що фінансово-правовий захист військовослужбовців – це особливий напрям фінансової діяльності держави, спрямований за забезпечення законності, достатності та стабільності отримання соціальних виплат військовослужбовцями.

It has been proven that the legality and sufficiency of the state’s financial activities for the social protection of military personnel in modern conditions in Ukraine depends on financial and legal regulation in the field of social policy. It has been noted that financial and legal protection, as an activity of the state for financial provision of social protection of military personnel, is based on the budget law, expenditures, which require coordination of the budgetary powers of the legislator and the Government on the formation and distribution of financial resources at the planning stage, as well as development and approval of the main financial law. The dependence of the financial state of the social protection of servicemen on the state financing of the directions and types of social policy of the state in the sphere of defense which requires legal regulation of the sources of financing of social payments of servicemen has been argued, as well as the distribution of the amounts of allocated funds and clarification of the powers of the involved subjects, in particular the legislator, the Government and managers budget funds. It has been determined that in order to improve the financial and legal foundations of social protection of servicemen, it is advisable to ensure two conditions: firstly, the introduction of a budget classification code of types of special social payments to servicemen in the expenditures of the State Budget of Ukraine, and secondly, compliance with the targeting of benefits, guarantees, compensations and other social payments, which are defined by the current legislation for military personnel and their family members. It has been substantiated that the justice and legality of meeting the interests of military personnel, as well as of all citizens related to social protection, are based on financial and legal principles.

На основании анализа действующего законодательства по финансированию социальных выплат военнослужащим и практики его применения определены проблемные вопросы их финансово- правового обеспечения. Отмечено, что реализация социальной функции государства по удовлетворению особых потребностей военных зависит от усовершенствования бюджетного процесса на стадиях составления проекта бюджета, рассмотрения и утверждения Закона о Государственном бюджете Украины. Определено, что финансово-правовая защита военнослужащих – это особое направление финансовой деятельности государства, направленное на обеспечение законности, достаточности и стабильности получения социальных выплат военнослужащими.
Financial and legal principles of social protection of military personnel
Keywords: фінансово-правовий захист; соціальні виплати; військовослужбовці; соціальний захист; публічні фінанси; бюджетні видатки; бюджетне законодавство; financial and legal protection; social payments; military personnel; social protection; public finances; budget legislation; финансово-правовая защита; социальные выплаты; военнослужащие; социальная защита; публичные финансы; бюджетные расходы; бюджетное законодательство